2015
DOI: 10.3892/mmr.2015.3950
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as an adjuvant for a Helicobacter pylori therapeutic vaccine

Abstract: The aim of the present study was to delineate the therapeutic effect of a Helicobacter pylori vaccine with chitosan as an adjuvant, as well as to identify the potential mechanism against H. pylori infection when compared with an H. pylori vaccine, with cholera toxin (CT) as an adjuvant. Mice were first infected with H. pylori and, following the establishment of an effective infection model, were vaccinated using an H. pylori protein vaccine with chitosan as an adjuvant. Levels of H. pylori colonization, H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 16 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…These results suggest that Tim-3 inhibited the activation of macrophages by negatively regulating the TLR4 signaling pathway. A previous study from this group (26) demonstrated that blocking Tim-3 with an inhibitory antibody upregulated TLR4 and MyD88 expression, promoted NF-κB activation, decreased the number of CD4 + CD25 + Foxp3 + Treg cells, and upregulated Th1 immune responses, resulting in intensified inflammation of the gastric mucosa of H. pylori-infected mice. Frisancho et al (11) reported that, in a mouse model of inflammatory heart disease, blocking Tim-3 significantly increases TLR4 expression and cardiac inflammation, indicating that Tim-3 is a negative regulator of the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 91%
“…These results suggest that Tim-3 inhibited the activation of macrophages by negatively regulating the TLR4 signaling pathway. A previous study from this group (26) demonstrated that blocking Tim-3 with an inhibitory antibody upregulated TLR4 and MyD88 expression, promoted NF-κB activation, decreased the number of CD4 + CD25 + Foxp3 + Treg cells, and upregulated Th1 immune responses, resulting in intensified inflammation of the gastric mucosa of H. pylori-infected mice. Frisancho et al (11) reported that, in a mouse model of inflammatory heart disease, blocking Tim-3 significantly increases TLR4 expression and cardiac inflammation, indicating that Tim-3 is a negative regulator of the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, natural polysaccharides as adjuvants are paving their way as a safe alternative, such as chitosan and Lycium barbarum polysaccharides (LBP). Earlier studies have demonstrated that H. pylori vaccine with chitosan as an adjuvant can protect against H. pylori infection and induce mixed Th‐cell responses . In addition, previous studies have shown that Lycium barbarum polysaccharides (LBP) can enhance T cell‐dependent antibody responses as an adjuvant .…”
Section: Discussionmentioning
confidence: 99%
“…30 Ovalbumin (OVA)/granulocyte-macrophage colony-stimulating factor-loaded chitosan NPs performed equivalently to IFA and CFA in the generation of OVA-specific antibody titer as well as CD4 + and CD8 + INF-γ + T cells. 31 Chitosan has been tested with hepatitis B virus surface antigen (HBsAg) 32 diphtheria toxin, Mycobacterium tuberculosis CFP10-TB10.4 fusion protein, 33 inactivated NIBRG-14 (H5N1) subunit antigen against influenza A, virus-like particles against norovirus, 34 against poliovirus, 35 against influenza A (H7N9, H9N2, H1N1, and H5N1) virus infection, [36][37][38] and against Helicobacter pylori 39 and has proved its potency as a successful adjuvant against these diseases. Gordon et al demonstrated that thermosensitive chitosan hydrogels possess higher ability to stimulate both humoral-mediated immunity and CMI, in addition to a slow and controlled in vitro release of antigen, compared to chitosan NPs, liposomes, and lipid-based cubosomes.…”
Section: Adjuvant Properties Of Chitosanmentioning
confidence: 99%